Beta-2-glycoprotein I Dependent Lupus Anticoagulants Form Stable Bivalent Antibody Beta-2-Glycoprotein I Complexes on Phospholipid Surfaces - Arnout, J.; Wittevrongel, C.; Vanrusselt, M.; Hoylaerts, M.; Vermylen, J. (Thrombosis and Haemostasis, 1998)
The precise mechanism by which Beta-2-glycoprotein I (β2GPI-) dependent lupus anticoagulants lengthen phospholipid-dependent clotting reactions is still poorly understood. In order to study this, murine monoclonal antibodies (moabs) against human β2GPI were raised. Eight of the 21 anti-β2GPI moabs, obtained from 2 fusions, fulfilled the criteria for lupus anticoagulant (LA) activity as tested with a variety of sensitive screening assays and confirmatory tests. Seven moabs did not influence any clotting test. The LA positive moabs were found to compete for similar or closely spaced epitopes on immobilized β2GPI. Two moabs with potent LA activity (moabs 22 F 6 and 22 B 3) and 1 moab without LA activity (moab 16 B 3) were selected to study the interaction between antibody, β2GPI and phospholipid. Interactions were investigated by real-time biospecific interaction analysis (BIA) based on plasmon surface resonance technology on a BIA-core instrument using a sensor chip coated with phospholipid. When 22 F 6, the moab with the most pronounced LA activity, was allowed to interact with the phospholipid surface at concentrations between 0 and 400 nmol/l, no appreciable binding could be detected. Likewise, no binding could be measured when β2GPI at concentrations between 0 and 400 nmol/l was passed over the phospholipid coated sensor chip. Combinations of β2GPI and 22 F 6 resulted in significant binding. Similar results were obtained with 22 B 3, another moab with LA activity. A LA negative Moab, 16 B 3, did not cause binding of antibody-β2GPI complexes. Fab’ fragments, derived from moab 22 F 6, inhibited the binding of β2GPI-22 F 6 and β2GPI-22 B 3 in a concentration dependent way, indicating that only bivalent β2GPI-antibody complexes bind with high affinity to phospholipids. Fab’ fragments, derived from moab 22 F 6, also inhibited the LA effect of moabs 22 F 6 and 22 B 3 in diluted plasma. In summary, these experiments indicate that the β2GPI-dependent LA effect depends on the formation of bivalent β2GPI-antibody complexes on phospholipid surfaces.